1990
DOI: 10.1128/jb.172.2.956-966.1990
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequences of genes encoding Acinetobacter calcoaceticus protocatechuate 3,4-dioxygenase: evidence indicating shuffling of genes and of DNA sequences within genes during their evolutionary divergence

Abstract: The DNA sequence of a 2,391-base-pair HindIII restriction fragment of Acinetobacter calcoaceticus DNA containing the pcaCHG genes is reported. The Protocatechuate 3,4-dioxygenase ( Fig. 1; EC 1.13.11.3) plays an essential role in the utilization of numerous aromatic and hydroaromatic compounds via the P-ketoadipate pathway (45). Ubiquity of the pathway in the natural environment is indicated by the fact that the enzyme is a trait universally shared by fluorescent Pseudomonas species (46) and by members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
92
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 51 publications
2
92
0
Order By: Relevance
“…In contrast, the TfdC enzyme shows a higher rate of conversion with 3,5-DCC as a substrate, which is in agreement with the findings of Pieper et al (22). In A. eutrophus JMP134, 3,5-DCC occurs as an intermediate in the conversion of 2,4-dichlorophenoxyacetic acid by enzymes of the tfd pathway (5), indicating that this pathway is specialized for conversion of 3,5-DCC (22 (10,13,17). The data presented here reinforce the hypothesis that the intradiol dioxygenases have a common ancestor.…”
supporting
confidence: 81%
“…In contrast, the TfdC enzyme shows a higher rate of conversion with 3,5-DCC as a substrate, which is in agreement with the findings of Pieper et al (22). In A. eutrophus JMP134, 3,5-DCC occurs as an intermediate in the conversion of 2,4-dichlorophenoxyacetic acid by enzymes of the tfd pathway (5), indicating that this pathway is specialized for conversion of 3,5-DCC (22 (10,13,17). The data presented here reinforce the hypothesis that the intradiol dioxygenases have a common ancestor.…”
supporting
confidence: 81%
“…Although the genes for 3,4-PCD have been cloned and expressed from both P. cepacia (61,62) and Acinetobacter calcoaceticus (24), their use in mutational studies would be limited by the amount and type of physical and mechanistic data available for the 3,4-PCDs encoded by these genes. In addition, the recombinant enzymes from these sources were not overexpressed or extensively characterized.…”
mentioning
confidence: 99%
“…In contrast, genes for such isofunctional enzymes have diverged substantially, as indicated by differences in G+C content of about 15% (9,20,27). Such differences in G+C content may be attributed in part to directional pressure exerted by mutations within divergent cell lines (32).…”
mentioning
confidence: 93%
“…The interaction of slipped DNA strands during mutation has been documented by demonstration that sequence-directed mutations create both deletions (3)(4)(5)(6) and repetitions of DNA sequence. Comparison of DNA sequences for oxygenative enzymes from A. calcoaceticus and P. putida suggested that slippage structures formed between misaligned DNA strands were formed by mutation and are maintained by mismatch repair during evolution (9,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation